The role of induction chemotherapy followed by surgery in unresectable stage IVb laryngeal and hypopharyngeal cancers: A case series - Pichit Sittitrai (2018)
© 2018 The Author(s). Background: The purpose of this study was to evaluate the benefit of induction chemotherapy followed by surgery in locally advanced unresectable stage IVb laryngeal and hypopharyngeal squamous cell carcinoma (LHSCC). Methods: Data of patients with stage IVb LHSCC who received induction chemotherapy for the purpose of tumor resection between January 2007 and January 2016 were retrospectively collected. Definitive surgery with postoperative adjuvant therapy was performed in patients whose tumors became resectable (resectable group). Chemoradiotherapy, radiotherapy, or supportive care was considered in patients whose tumors remained unresectable (unresectable group). Results: Thirty-two patients were identified; the tumor resectability rate after induction chemotherapy was approximately 56%. The median overall survival (OS) rates of the resectable and unresectable groups were 20.0 months (range, 16.0-35.5 months) and 9.5 months (range, 6.0-15.0 months), respectively (p = 0.008). The estimated 2-year OS rates of the resectable and unresectable groups were 59.5% (95% confidence interval [CI], 33.2-78.3%) and 10.7% (95% CI, 1.1-35.4%), respectively (p = 0.008). The estimated 2-year disease-free survival (DFS) rates of the resectable and unresectable groups were 53.5% (95% CI, 27.9-73.6%), and 14.3% (95% CI, 2.3-36.6%), respectively (p = 0.009). On multivariate analysis, factors positively impacting OS and DFS in all patients were surgical resection, a laryngeal primary site, and induction chemotherapy with docetaxel, cisplatin, and fluorouracil. Conclusions: In advanced unresectable stage IVb LHSCC patients, surgical resection following induction chemotherapy appears to improve survival outcomes.